Oplodna sječa u šumi hrasta lužnjaka i poljskog jasena u Srijemu i njene specifičnosti - Bobinac, Martin (Array, 2007)
The silvicultural-technological procedures in the regeneration of the stands of common oak and narrow-leaved ash with common maple and Tartar maple were researched in the area of Srem. regeneration.